Determinants of Comprehensive Understanding of Stunting among Indonesian Pregnant Women and Mothers of Toddlers Aged 0–23 Months in 2023 - Silalahi, Agnes Rosihan Kristianti; Rahani, Rini (Politeknik Statistika STIS, 2025)
Stunting is a chronic nutritional disorder that remains a priority in Indonesia. As withthe second goal of the SDGs (zero hunger), the Ministry of Health (MoH) has implemented acommunication strategy for behavioural change and community empowerment through a classprogram for pregnant women and mothers of toddlers class using the Maternal and Child Health(MCH) book. However, it is still not optimal to increase the understanding of stunting. The 2023Indonesian Health Survey (IHS) shows that women in Indonesia still have a poor comprehensiveunderstanding of stunting. It has includes pregnant women and breastfeeding mothers as keytarget groups for stunting reduction. This study aims to describe and analyse the characteristicsof Indonesian pregnant women and mothers of toddlers aged 0–23 months that significantlyinfluence their comprehensive understanding levels of stunting. Data from 2023 IHS wereanalysed using descriptive statistics with graph and table, together with inferential analysisthrough ordinal logistic regression using the Proportional Odds Model (POM). The result showsthat the majority of these mothers have a poor level of comprehensive understanding of stunting,with five variables having a significant influence, namely: access to information, education level,employment status, socioeconomic status, and residence area.